Pyrrhocoris apterus as a bioindicator of the environmental state - Корж, О. П. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2013)
It has been determined that presence of bedbugs in the territory can tell about the state of the environment. In the territories with maximal anthropogenic pressure (e.g. industrial area), these insects are not found or have low numbers. It has been found that Rivne population firebugs are greater by most of morphometric indices examined than bedbugs from Zaporozhye. Under difficult conditions of existence we have observed not only reduction of bedbugs in size but also changes in the proportions of their bodies. This is accompanied by increasing of insect polymorphism.